Electro-hydrodynamic shooting phenomenon of liquid metal stream - Fang, Wen-Qiang; He, Zhi-Zhu; Liu, Jing (Applied physics letters, 2014)
We reported an electro-hydrodynamic shooting phenomenon of liquid metal stream. A small voltage direct current electric field would induce ejection of liquid metal inside capillary tube and then shooting into sodium hydroxide solution to form discrete droplets. The shooting velocity has positive relationship with the applied voltage, while the droplet size is dominated by the aperture diameter of the capillary nozzle. Further, the motion of the liquid metal droplets can be flexibly manipulated by the electrodes. This effect suggests an easy going way to generate metal droplets in large quantity, which is important from both fundamental and practical aspects.